Caregiver burden dan kualitas hidup: Kajian studi pada ibu yang memiliki anak autisme spectrum disorder - Ridzkina, Siti Meisarah (JIWA: Jurnal Psikologi Indonesia, 2024)
Caring for a child with Autism Spectrum Disorder presents challenges and obstacles for every parent, especially mothers, because their role is more closely related to being the main caregiver for the child so that they are vulnerable to feeling both physical and psychological fatigue, which can trigger the emergence of caregiver burden in themselves, which will have an impact on reducing their quality of life. This study aimed to determine the relationship between caregiver burden and quality of life in mothers of children with Autism Spectrum Disorder (ASD) in Banda Aceh City. A total of 62 mothers who have ASD children in Banda Aceh City were involved as research samples selected using the Quota Sampling technique. Data were collected using the Quality of Life Autism-Parent Version and the Zarit Burden Interview-New Short Version. Analysis of research data using Jeffrey's Amazing Statistics Program, where the results of the analysis show that there is a negative relationship between caregiver burden and quality of life in mothers who have ASD children in Banda Aceh City, which means that the higher the caregiver burden felt, the lower the quality of life in mothers who have ASD children, and vice versa, the lower the caregiver burden felt, the higher the quality of life.